Analysis of Efforts to Reduce Production Costs at Nafa’s Bakery Tulangan using Target Coasting: Analisa Upaya Pengurangan Biaya Produksi pada Nafa Bakery Tulangan menggunakan Target Coasting - Firmansyah, Prayoga Dwi; Rahadian Trisna Kusuma; Ribangun Bamban Jakaria; Doni Prasetyo (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Target costing is the process of determining the standard price of a product according to the company's wishes (target) as a basis for determining the selling price of the product in order to achieve the company's desired profits. This is very easy for companies to implement, allowing them to better control costs (cost management) and achieve company profits. The aim of this research is to determine the impact of implementing target costing on increasing production cost efficiency and increasing gross profit. The research method used is descriptive and qualitative. The results of the research, namely the target costing calculation at Nafa Bakery Tulangan, show that there is efficiency when the company has a gross profit of Rp. before applying the target costing method. By using the target cost method, gross profit increased by IDR 230,128,704. In other words, the difference in gross profit increase is IDR 4,472,832. The suggestion is that companies should use the target cost method because it can produce more efficient gross profits.